2022
DOI: 10.1002/hon.3087
|View full text |Cite
|
Sign up to set email alerts
|

Circulating cell‐free DNA for target quantification in hematologic malignancies: Validation of a protocol to overcome pre‐analytical biases

Abstract: Circulating tumor DNA (ctDNA) has become the most investigated analyte in blood. It is shed from the tumor into the circulation and represents a subset of the total cell‐free DNA (cfDNA) pool released into the peripheral blood. In order to define if ctDNA could represent a useful tool to monitor hematologic malignancies, we analyzed 81 plasma samples from patients affected by different diseases. The results showed that: (i) the comparison between two different extraction methods Qiagen (Hilden, Germany) and Pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 52 publications
0
2
0
Order By: Relevance
“…In addition, testing IGH and IGK clonality on biopsy samples has shown that up to 83% of DLBCL carry an immunoglobulin molecular marker, which can be monitored on ctDNA by NGS and is associated with prognosis and prediction of relapse ( 62 ), also in new therapeutic contexts such as chimeric antigen receptor T (CAR-T) cell therapy ( 65 ). In this setting, a NGS based approach could overcome some limitations represented by unproductive IGH rearrangements, the variable and generally low amount of cfDNA extracted from plasma and a relapse with a different clone from the baseline one ( 19 , 62 ).…”
Section: Ddpcr In Chronic Lymphoid Malignanciesmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, testing IGH and IGK clonality on biopsy samples has shown that up to 83% of DLBCL carry an immunoglobulin molecular marker, which can be monitored on ctDNA by NGS and is associated with prognosis and prediction of relapse ( 62 ), also in new therapeutic contexts such as chimeric antigen receptor T (CAR-T) cell therapy ( 65 ). In this setting, a NGS based approach could overcome some limitations represented by unproductive IGH rearrangements, the variable and generally low amount of cfDNA extracted from plasma and a relapse with a different clone from the baseline one ( 19 , 62 ).…”
Section: Ddpcr In Chronic Lymphoid Malignanciesmentioning
confidence: 99%
“…They are applied to different tissues or compartments, i.e. bone marrow (BM) and peripheral blood (PB) - for both genomic DNA from circulating neoplastic cells or circulating cell-free DNA (cfDNA) from plasma ( 18 , 19 ).…”
Section: Introductionmentioning
confidence: 99%